Corporate governance : principles, policies and practices - Tricker, Bob (Oxford universityn press, 2009)
Corporate Governance: Principles, Policies and Practices provides a comprehensive understanding of the major aspects of corporate governance. The author presents an overview of theories, models, processes and issues which make up this constantly developing subject area.